Bilateral cataract surgery in a Japanese macaque (Macaca fuscata): A case report. Issue 11 (19th November 2021) - Miwa, Yukihiro; Komatsu, Hiroyuki; Shinojima, Ari; Oda, Ayako; Inagaki, Mao; Usami, Kensuke; Akasaka, Minori; Kobayashi, Yoshitaka
Abstract: A 7.5‐year‐old intact male Japanese macaque was presented for evaluation of vision loss. After a complete ophthalmic examination, the patient was diagnosed with hypermature cataract in both eyes. After the cataract surgery, it was able to locate food and walk in a straight line. Abstract : This is the first report on cataract surgery in a Japanese macaque. Good vision was restored postoperatively by calculating the intraocular lens power and performing the surgery properly even if there was a hypermature cataract.